The competition numbers of Johnson graphs with diameter four - Kijung Kim (Electronic Journal of Graph Theory and Applications (EJGTA), 2017)
In 2010, Kim, Park and Sano studied the competition numbers of Johnson graphs. They gave the competition numbers of J(n,2) and J(n,3).In this note, we consider the competition number of J(n,4).